Selective associative phonagnosia after right anterior temporal stroke. (31st July 2018) - Luzzi, Simona; Coccia, Michela; Polonara, Gabriele; Reverberi, Carlo; Ceravolo, Gabriella; Silvestrini, Mauro; Fringuelli, Fabio; Baldinelli, Sara; Provinciali, Leandro; Gainotti, Guido
Abstract: We report the case of a 48 year old men who developed a selective impairment in famous voice recognition after ischemic stroke in right subcortical structures (lenticular nucleus and head of the caudate) and right anterior temporal lobe. He underwent fibrinolytic treatment. During the following days he progressively recovered and was discharged without neurological focal sign. Patent foramen ovale was found. When he got back to his house he noticed that he was unable to recognize the voice of his favoured singers and needed to ask who was the singer to his relatives. Neuropsychological examination revealed a selective impairment in famous voice recognition in the absence of alteration of voice perception, face perception and famous face recognition. All other neuropsychological domains were spared. In particular language, memory and executive functions were intact. Neuroimaging carried out by means of PET and MRI revealed two small ischemic lesions in the right subcortical region, involving lenticular and caudate nuclei and in the right temporal pole. To our knowledge, this is the first case described in literature of a patient showing a selective associative phonagnosia after right anterior temporal stroke. The present case helps to clarify the brain circuits underlying famous voice recognition and adds evidence in favour of a right hemisphere involvement in processing knowledge of familiar voices. These findings are discussed in relation to current models of brain organization of person-specific and general semantic knowledge. Highlights: A selective impairment in famous voice recognition was found after right ATL stroke. No defect was found in voice perception, face perception and famous face recognition. PET and MRI revealed small lesions in right subcortical nuclei and temporal pole. From the temporal pole the lesion extended posteriorly in the middle temporal gyrus.